Les Personnes Déplacées de la Corne de l’Afrique - Mputu, Jean-Pierre (Refuge: Canada’s Journal on Refugees, 1994)
Human suffering within the Horn has become endemic. The multidimensional crisis that has surrounded the region for decades has been exacerbated by inter- and intra-ethnic violence, conflicts and wars. These conflicts and wars have had disastrous social, economic, political and environmental consequences - in particular human displacement within the Horn. This paper defines new categories of refugees. The author questions whether displaced people in the Horn are Convention refugees, environmental refugees or simply economic migrants. The problems that they face in the first country of asylum and the resettlement country are discussed.